Analisis Pengaruh Pengungkapan CSR Terhadap Kepuasan Investor pada Perusahaan Sektor Tambang yang Terdaftar di BEI - Ditta Happyani; Sobrotul Imtikhanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
CSR disclosure is measured using an index score based on the Global Reporting Initiative (GRI) guidelines, while investor satisfaction is represented by stock returns. The research method employed is a quantitative approach using simple linear regression analysis. The t-test results show that CSR disclosure has a positive and significant effect on investor satisfaction, with a significance value of < 0.001. Furthermore, the coefficient of determination (R²) of 0.928 indicates that 92.8% of the variation in investor satisfaction can be explained by CSR disclosure. These findings reinforce the evidence that good CSR practices can enhance investor trust and satisfaction, especially in industries with high environmental risk.